Navigating Non‐Invitation: Pro‐Vaccine Choice Communities Amidst Exclusion and Public Participation - Barbara Morsello; Paolo Giardullo (Social Inclusion)
Between 2017 and 2021, specific health policy concerning vaccination in Italy contributed to the “non‐invitation” of pro‐vaccine choice communities to decision‐making processes and public services with significant consequences for their societal life. This situation led to the emergence of new, often barely visible, participatory pathways. This article aims to examine the dynamics of exclusion and participation of pro‐vaccine choice communities in Italy, adopting a science and technology studies (STS) framework that allows us to explore how non‐invitation and participation are deeply entangled. Through digital ethnography and interviews, we investigate how individuals and communities navigate “non‐invitation” and seek alternative avenues for participation. We observe their efforts to contest compulsory vaccination policies and legitimize their claims through political representation and independent scientific research. Despite facing stigmatization and marginalization, they employ various strategies to influence decision‐making processes. However, challenges persist due to public stigmatization and punitive measures. Our findings highlight the nuanced interplay between dissenting perspectives, exclusionary practices, and participatory strategies in public health debates. The study underscores the ambivalence of participatory processes in knowledge societies, where participation and non‐invitation often coexist, shaping the contours of public discourse and policy agendas.